Urgensi Penetapan Peraturan Pemerintah tentang Pidana Kerja Sosial di Indonesia Berdasarkan KUHP Baru - Laia, Filpan Fajar Dermawan (CV. Social Politic Genius (SIGn), 2024)
This research aims to contribute by providing a conceptual framework for drafting government regulations on community service sentences from an Indonesian criminal law perspective while also drawing comparisons with practices in Canada and the Netherlands. A normative legal research method is employed, involving a qualitative analysis of the collected legal materials. The findings indicate that community service sentences in Law Number 1 of 2023 signify a paradigm shift in the Indonesian criminal justice system towards a more humane and restorative approach. Comparisons with Canada and the Netherlands offer valuable insights into the effective and just imposition of community service sentences. The principles of restorative justice and utilitarianism, along with the comprehensive regulations in the Canadian Criminal Code and the Wetboek van Strafrecht, can serve as references in formulating robust government regulations in Indonesia. The urgency of establishing these government regulations is underpinned by the need for legal certainty, human rights protection, and optimization of the benefits of community service sentences for convicted individuals, ensuring that this sentence is not merely an alternative punishment but also an effective instrument in achieving the rehabilitation and social reintegration of offenders. Therefore, it is recommended that the Government promptly formulate Government Regulations on community service sentences, considering best practices from other countries and paying attention to relevant laws. It is also recommended that the House of Representatives consider amending Law Number 8 of 1981 regarding the regulation of community service sentence implementation to ensure harmony and legal clarity between the Criminal Procedure Code and the New Penal Code and to provide a solid legal basis for the Public Prosecution Service in carrying out its supervisory duties.